Financial Feasibility Analysis of Asphalt Mixing Plant Investment: A Case Study in Gianyar Regency, Bali - Jayantara, I Wayan Putra (Universitas Pendidikan Nasional, 2025)
The availability of adequate road infrastructure is crucial for supporting mobility and regional economic growth. In Indonesia, increasing demand for high-performance roads has driven a transition from penetration macadam to hot mix asphalt (HMA). To meet this demand efficiently, reliable production facilities such as Asphalt Mixing Plants (AMP) are essential. This study aims to evaluate the financial feasibility of an AMP investment located in Pering Village, Blahbatuh District, Gianyar Regency, Bali. The analysis uses five financial indicators: Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Break Even Point (BEP), and Annual Equivalent (AE). Financial data were collected from the company’s records of hotmix production and sales during the 2014–2020 period. The results indicate that the AMP project is financially viable. The NPV is Rp. 33.421.961.979, the IRR is 18% higher than the Minimum Attractive Rate of Return (MARR) of 16%—while the BEP was achieved in the 7th month of 2015. The AE value reached Rp. 4.774.565.997 per year, and the BCR was calculated at 1,244. These findings confirm that the investment is profitable and worth pursuing. This study provides practical insights for investors and stakeholders in making data-driven decisions for infrastructure investments, particularly in the road construction sector. Furthermore, the findings are relevant for long-term AMP business development, considering the growing demand for HMA in Indonesia. The shift from penetration macadam to HMA underscores the importance of efficient asphalt production facilities to ensure consistent supply and support sustainable infrastructure development.